Modeling of the system of regional indicators of the development of a circular economy (Nexo Revista Científica, 2023)
The purpose of the article is to present a methodological approach to modeling the system of regional indicators in the context of the development of the closed-cycle economy. The employed research methods rely on the provisions of economic and statistical analysis, management theory, situational and adaptive approaches in management, system analysis, simulation modeling, the theory of finance and financial markets, and the theory of taxation. The authors emphasize the importance of accounting for such factors as finance, taxation, entrepreneurial infrastructure, and education for the successful implementation of closed-loop economy strategies at the regional level. The results of modeling the system of regional indicators clarify the estimated forecast of the consequences of the adopted managerial decisions in the financial and industrial policy for the introduction of technologies.